Citral and Geraniol: Two Novel and Potent Noncarcinogenic Terpene Alternatives to Alcohol-Based Mouthwashes against Cariogenic Oral Bacteria - Narayanan, Nirupama; Charlton, Stephanie; Martinez, Nathalie; Sandilands, Erica; Torres, Chelsea (European Journal of General Dentistry, 2025)
Several recent studies have linked the high incidence of oral cancer among users with a history of prolonged use of alcohol-based mouthwashes, due to increased topical acetaldehyde, a carcinogen made from alcohol breakdown. Our research has previously shown that two volatile oils, Cymbopogonwinterianus (Lemon grass) and Cymbopogonflexuosus (Citronella Java), exhibit significant antibacterial activity on four commonly occurring cariogenic oral bacteria. We have also demonstrated that these oils are mainly composed of four terpenes: citronellal, citronellol, geraniol, and citral. In this follow-up study, we wanted to determine which of these specific terpene constituents was responsible for the antibacterial activity of these two volatile oils.In this study, we tested these terpenes on our selected panel of oral bacteria, namely Micrococcusluteus, Streptococcussalivarius, Streptococcusmutans, and Enterococcusfaecalis in several qualitative assays such as Kirby–Bauer disc diffusion, minimum inhibitory concentration determination, minimum bactericidal concentration determination, and time-kill kinetics to evaluate their effectiveness as antibacterial agents.Citral and geraniol emerged as the most potent broad-spectrum antibacterial agents among all four terpene candidates. More specifically, citral was most effective on both oral streptococcal strains followed by geraniol, while geraniol exhibited the highest antibacterial activity against E. faecalis. Both terpenes showed a similar pattern of killing as seen with oral streptococci when tested against M. luteus.We hypothesize that these two terpenes may serve as safer, better alternatives to alcohol-based mouthwashes.
Keywords: volatile oils; alcohol-based mouthwashes; microbiota; terpenes; acetaldehyde